Society’s Response to Environmental Challenges: Citizenship and the Role of Knowledge (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
As human beings we ultimately depend on the services that ecosystems provide, such as food production, nutrient recycling and flood buffering, hence, current losses of such ecological goods and services and necessary ecological conditions constitute a real threat.  The interdependence of society and nature, the inherent complexity of such social-ecological systems and the rapid deterioration of ecosystem services across the globe provide the rationale for a growing body of literature focused on sustainability and the importance for societies to build capacity in dealing with these issues.